1998
DOI: 10.1017/s0266467498000157
|View full text |Cite
|
Sign up to set email alerts
|

Changes in small mammal assemblage structure across a rain forest/open forest ecotone

Abstract: ABSTRACT. The effect of the change in vegetation structure from closed rain forest to tall open forest on the small mammal assemblage was studied by live trapping at three sites where the ecotone was very narrow (<20 m) near the southern end of the Wet Tropics World Heritage Area of Australia. Habitat heterogeneity was significantly higher in the mixed open forest/ecotone area than in the adjacent rain forest. There was a large change in the structure of the small mammal assemblage coincident with the vegetati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
19
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 16 publications
5
19
0
Order By: Relevance
“…When true structural diversity has been measured it often fails to account for species richness in rodent systems. For example, when structural characteristics such as canopy height, canopy density, and tree diameter at breast height are used to predict the diversity of tropical rodent communities, no significant relationships emerge (August 1983;Williams and Marsh 1998). Such patterns are consistent in systems of both tall stature (August 1983;Williams and Marsh 1998) and low stature (Bond et al 1980) and mirror those in this Mojave Desert rodent system.…”
Section: Discussionmentioning
confidence: 98%
“…When true structural diversity has been measured it often fails to account for species richness in rodent systems. For example, when structural characteristics such as canopy height, canopy density, and tree diameter at breast height are used to predict the diversity of tropical rodent communities, no significant relationships emerge (August 1983;Williams and Marsh 1998). Such patterns are consistent in systems of both tall stature (August 1983;Williams and Marsh 1998) and low stature (Bond et al 1980) and mirror those in this Mojave Desert rodent system.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies (Williams 1990, Laurance 1994, Williams and Marsh 1998 have shown that the vertical stratification of foliage density is significantly related to the structure of small-mammal assemblages in the rain forests of the Wet Tropics. Therefore, trapping grids were placed to include as much variability in the vegetation structure as possible within each site.…”
Section: Methodsmentioning
confidence: 99%
“…Habitat heterogeneity can have many dimensions, but all dimensions affect either the architectural complexity or the spatial and temporal heterogeneity of the habitat (Southwood 1996). Considerable research has been conducted on the relationships between habitat structure and mammal assemblage structure (e.g., M'Closkey 1976, Fox 1981, August 1983, Shenbrot et al 1994, Williams and Marsh 1998, Fox and Fox 2000. Generalities have been elusive, however, and some researchers have cast doubt on the validity of applying findings from local-scale studies to larger spatial scales (Ricklefs 1987, Levin 1992, Marquet 1994, Hughes et al 1999.…”
Section: Introductionmentioning
confidence: 99%
“…Heterogeneity refers to the lateral extent of vegetation coverage, while complexity refers to the vertical layering of vegetation ( sensu August, 1983). Increased vegetation heterogeneity has been shown to correspond to increases in species diversity amongst small mammals (Williams & Marsh, 1998). Vegetation heterogeneity is therefore likely to increase the representation of different kinds of mammalian species within an ecosystem (similarly, complexity would also increase representation; however, this is not dealt with further here).…”
Section: Introductionmentioning
confidence: 99%